STILL PICTURE EXTRACTING METHOD AND IMAGE PROCESSING DEVICE FOR IMPLEMENTING THE METHOD - OGURA YASUNOBU (2016)
PROBLEM TO BE SOLVED: To provide a still picture extracting method that can extract still pictures at imaging positions spaced from one another at an equal distance in a short time.SOLUTION: A still picture extracting method performs an operation of extracting plural first frames contained in a moving picture stream, and achieving the imaging time of each of the plural extracted first frames, an operation of specifying the imaging position of a camera at the imaging time of each of the plural first frames from the plural first frames, an operation of estimating the imaging time of each of plural frames obtained by imaging at plural imaging positions spaced from one another at an equal distance on the basis of the imaging position specified for each of the plural first frames and the achieved imaging time, and an operation of extracting, from the moving picture stream, a second frame at the estimated imaging time as each of plural frames obtained by imaging at the plural imaging positions spaced from one another at an equal distance.SELECTED DRAWING: Figure 1 【課題】距離が等間隔に離れた撮影位置における静止画像を短時間で抽出することができる静止画像抽出方法を提供する。【解決手段】動画像ストリームに含まれる複数の第１のフレームを抽出するとともに、抽出した複数の第１のフレームそれぞれの撮影時刻を取得する動作と、複数の第１のフレームそれぞれの撮影時刻におけるカメラの撮影位置を複数の第１のフレームから特定する動作と、複数の第１のフレームそれぞれで特定された撮影位置と、取得された撮影時刻とに基づいて、距離が等間隔の複数の撮影位置で撮影することによって得られる複数のフレームそれぞれの撮影時刻を推定する動作と、推定された撮影時刻の第２のフレームを、距離が等間隔の複数の撮影位置で撮影することによって得られる複数のフレームそれぞれとして動画像ストリームから抽出する動作とを行うものである。【選択図】図１